2012
DOI: 10.1109/tits.2012.2204053
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Adaptive Cruise Control Implementation of Team Mekar at the Grand Cooperative Driving Challenge

Abstract: This paper presents the cooperative adaptive cruise control implementation of Team Mekar at the Grand Cooperative Driving Challenge (GCDC). The Team Mekar vehicle used a dSpace microautobox for access to the vehicle controller area network bus and for control of the autonomous throttle intervention and the electric-motor-operated brake pedal. The vehicle was equipped with real-time kinematic Global Positioning System (RTK GPS) and an IEEE 802.11p modem installed in an onboard computer for vehicle-to-vehicle (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 15 publications
1
35
0
1
Order By: Relevance
“…This competition revealed some of the most important problems to be solved before bringing this technology into production, including the communication systems reliability. From the control point of view, most of the implementations were based on proportional, proportional-derivative feedback/feedforward controllers [13], [14], [15] or Model Predictive Control (MPC) techniques [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…This competition revealed some of the most important problems to be solved before bringing this technology into production, including the communication systems reliability. From the control point of view, most of the implementations were based on proportional, proportional-derivative feedback/feedforward controllers [13], [14], [15] or Model Predictive Control (MPC) techniques [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…It shall be noted that the accuracy of the relative position parameters are very critical for vehicle platooning implementation, especially for the communicated-GPS-only platoon system [143]. Many related studies have been focusing on improve the GPS precision.…”
Section: A Deployment Of Platoon-based Driving Patternmentioning
confidence: 99%
“…Levent Guvence et al [14] have done an on road experimentation in the CACC implementation of Team Maker in the Grand Cooperative Driving Challenge (GDCC) using vehicles equipped with sensors, actuators and control units. The experimental results showed that Global Positioning System (GPS) information can be used to implement ACC and CACC.…”
Section: State Of Artmentioning
confidence: 99%